Analisis Kesejahteraan Psikologis Karyawan dan Kualitas Interaksi Bawahan Berdasarkan Kepribadian Atasan - Nuri Sadida; Nurindah Fitria (HUMANITAS: Indonesian Psychological Journal, 2018)
This research background was the low indicator of employee well-being (EWB) in Jakarta that derived from several employee surveys. One factor that has significant influence to EWB is management leadership. The aims of this research are to test the correlation between leader-member exchange and employee well-being, and to test correlation between leader's personality type and leader-member exchange. Participants involved in this study are 72 employees, that was taken using accidental sampling. This research adopted LMX7 scale to measure the leader-member exchange, EWB tool based on Juniper theory (2010) to measure employee well-being, and DISC personality to measure personality type. Result showed there is a significant correlation between leader-member exchange and employee well being, and there is correlation between leader's personality type, specifically type C and S with leader-member exchange. This result can be used for Human Resources Management to consider employee with type C and S to fill position as middle level manager.